Utility of multiplex real-time PCR in the diagnosis of extrapulmonary tuberculosis - Reena Raveendran; Chand Wattal (Brazilian Journal of Infectious Diseases, 2016)
Objective: The diagnosis of extrapulmonary tuberculosis is still a challenge because of its pauci-bacillary nature. The aim of the study was to evaluate the role of a multiplex PCR assay in the diagnosis of extrapulmonary tuberculosis and to compare the efficiency of two targets, IS6110 and MPB64 to detect Mycobacterium tuberculosis. Methods: 150 extrapulmonary samples (61 pus/aspirate, 46 tissue, 32 body fluids, and 11 urine) from clinically suspected cases of tuberculosis were included in the study. All the samples were subjected to direct fluorescent microscopy, TB culture (BacT/ALERT 3D, biomerieux, Durham, North Carolina, USA) and a Multiplexed Tandem PCR targeting two mycobacterial DNA sequences, IS6110 and MPB64. Master-Mix reagents and primers were prepared by AusDiagnostics Pvt. Ltd (Alexandria, New South Wales, Australia). The performance of the assay was assessed using a composite gold standard, which included clinical characteristics, microbiology smear as well as culture, histopathology, cytology, radiology, and response to antitubercular therapy. Results: 20.3%, 23.6%, and 45.3% of specimens were positive by smear, culture, and PCR, respectively. The sensitivity and specificity of the multiplex PCR was 91.9% and 88.4%, respectively, using the composite gold standard. Positive and negative predictive values of the PCR were estimated as 85.1% and 93.8%, respectively. Higher positivity was observed with target IS6110 (44.6%) as compared to target MPB64 (18.9%). The sensitivities of IS6110 and MPB64 individual targets were 90.3% and 64.5%, respectively, and specificities were 88.4% and 97.7%, respectively. Conclusion: PCR can play an important role in rapid and accurate diagnosis of extrapulmonary tuberculosis. IS6110 alone is an effective target in our part of the country. Keywords: Extrapulmonary tuberculosis, Multiplex PCR, IS6110, MPB64